Support Group dalam Menurunkan Tingkat Stres pada Caregiver Skizofrenia - Risca Aulia; Katrim Alifa Putrikita (LPPM Universitas Abdurrab, 2024)
One of the cases experienced by schizophrenia caregivers is stress. One intervention to reduce stress levels in schizophrenia caregivers is a support group. Support groups are carried out with peer groups who have relatively similar problems by sharing information about the problems experienced by schizophrenia caregivers. This research aims to reduce the level of stress felt by caregivers of schizophrenia, using a quasi-experiment and using 6 research subjects consisting of 5 female subjects and 1 male subject who have moderate to severe stress level scores. The data collection method was carried out using the Kingston Caregiver Stress Scale (KCSS) and analysis used the Repeated Measured Anova Test. The results of the support group intervention showed that caregivers experienced significant changes (p<0.05) in terms of reducing stress levels before and after providing support group therapy. This study has important implications for the implementation of support groups in reducing stress levels among caregivers of individuals with schizophrenia. It can be concluded that support groups are effective in lowering stress levels in schizophrenia caregivers.